2019
DOI: 10.1108/ijm-09-2018-0307
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of deviant behaviors in the physical work environment

Abstract: Purpose The purpose of this paper is twofold: first, the relationship between crowding perceptions (i.e. employees’ perceptions of insufficient personal space due to offices’ physical constraints) and deviant workplace behaviors (DWBs) directed at both the organization as a whole (DWB-O) and individuals (DWB-I); and second, privacy invasion from supervisors and peers as a mediator. Design/methodology/approach Data were collected from 299 respondents working in open-plan offices at four medium-to-large sized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Kim and de Dear also found that satisfaction with the amount of available workspace influences employees' overall perceptions of the workspace [59]. In addition to satisfaction and productivity, crowding affects deviant workplace behaviors, such as violent and antisocial behavior [60,61]. All of these results show that how workers feel about the amount of their workspace has a profound effect on their well-being and productivity.…”
Section: Feelings Of Crowding In the Work Environmentmentioning
confidence: 87%
See 1 more Smart Citation
“…Kim and de Dear also found that satisfaction with the amount of available workspace influences employees' overall perceptions of the workspace [59]. In addition to satisfaction and productivity, crowding affects deviant workplace behaviors, such as violent and antisocial behavior [60,61]. All of these results show that how workers feel about the amount of their workspace has a profound effect on their well-being and productivity.…”
Section: Feelings Of Crowding In the Work Environmentmentioning
confidence: 87%
“…As previously mentioned, there is ample evidence that crowding feelings in the workplace affect workers' perceptions and behaviors [44,[58][59][60][61]. Our second and third hypotheses were determined to examine these relationships in the WFH context.…”
Section: H1mentioning
confidence: 99%
“…Considering these negative implications, why would employees undertake counterproductive work activities? Previous studies answer the question by identifying various resource-draining factors that may encourage employees to harm their company, such as family-to-work conflict (Ferguson et al , 2012), hindrance job stressors (Zhang et al , 2018), organizational injustice (Kakavand et al , 2020) or perceptions of insufficient physical space in offices (Zoghbi-Manrique-de-Lara and Sharifiatashgah, 2019). A common theme underlies these determinants: They all cause frustration for employees related to the quality of their professional functioning, to which they react with negative behaviours to try to unleash their frustrations (Zhang et al , 2018).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…On a global scale, the recent trend in the US concerns transformation toward sustainable offices that promote productivity and provides more attention to workers and their performance dimensions. Employees' ability to control the working environment, such as lighting and visual quality, has been associated with the level of satisfaction, including happiness, alertness, and mood [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%